Dietary lipids induce PPARd and BCL6 to repress macrophage IL-23 induction after intestinal injury and LPS exposure - Ashleigh M. Gil; Daniel F. Zegarra-Ruiz; Wan-Jung Wu; Kendra Norwood; Adrien Assie; Buck S. Samuel; Angela M. Major; Gretchen E. Diehl; Andrea A. Hill McAlester (Scientific Reports)
Abstract Unresolved tissue damage is a common feature of Inflammatory Bowel Disease (IBD) that facilitates disease progression. Here, we showed that high animal fat diets (HFD), an environmental risk factor associated with IBD pathogenesis, suppress intestinal macrophage production of critical tissue repair responses after damage. This includes reduced IL-23 production, which drives downstream production of IL-22, which is needed for barrier repair. Indicating that dietary lipids interfere with responses to microbial molecules needed to induce barrier protective functions, we found oleic acid could directly suppress macrophage Il23a induction after lipopolysaccharide (LPS) treatment. Deleting the lipid transporter CD36 on macrophages restored the Il23a and Il22 response, reducing intestinal damage in HFD-fed DSS-treated mice. We found that CD36-mediated intracellular lipid accumulation, mainly oleic acid, in macrophages leads to peroxisome proliferator-activated receptor delta (PPARδ) release of the transcriptional repressor protein B-cell lymphoma 6 (BCL6). BCL6 suppresses Il23a transcription in microbe-exposed macrophages. The studies suggest dietary lipid modulation of the macrophage PPARδ/BCL6 transcriptional repressor complex is a key mechanism of fat-associated defects in intestinal damage repair and immune dysregulation. Overall, our findings provide new insights into dietary lipid contribution to intestinal disease progression and identify new potential therapeutic targets to decrease diet-associated risk for IBD.